2019
DOI: 10.33503/ebio.v4i02.437
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi buku petunjuk praktikum biokimia berbasis inkuiri terbimbing untuk meningkatkan kemampuan kerja ilmiah

Abstract: Learning material is one of the facilities needed by students to help them find concepts and answers to their problems. There are various types of learning materials, one of which is a practical guide. Based on observations on learning materials and the learning process of Biochemistry courses at IKIP Budi Utomo Malang shows that there are no practical manuals developed and students' scientific workability is low. The aim of the research is to improve students' scientific work abilities through the implementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
4
0
2
Order By: Relevance
“…Computers and other educational technology facilities can make students discuss ideas, help their peers, and learn independently with different innovations (Arsyad, 2013). This provides an opportunity for students or students to communicate their understanding and understanding of Biochemistry subjects and can build creative ideas in learning (Widyaningrum & Wijayanti, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Computers and other educational technology facilities can make students discuss ideas, help their peers, and learn independently with different innovations (Arsyad, 2013). This provides an opportunity for students or students to communicate their understanding and understanding of Biochemistry subjects and can build creative ideas in learning (Widyaningrum & Wijayanti, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Inquiry-based manual laboratory. Classroom action research conducted by (Widyaningrum & Wijayanti, 2019) also shows that the use of guided inquiry-based biochemistry practicum books is effective in improving students' scientific work ability. In addition, the use of practicum guides can also increase student motivation in carrying out these practicum activities according to the results of research that has been conducted by (Kenengsih, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…Several previous studies have shown that the use of a guided inquiry-based practicum guide can help increase student activity and motivation in doing practicum (Handayani, F, & Anhar, 2014;Lubis, Silaban, & Jahro, 2016;Nengsi, 2016;Umah, Sudarmin, & Dewi, 2014;Waluyo & Parmin, 2014). In addition, it also helps train students' scientific work skills (Kenengsih, 2017;Widyaningrum & Wijayanti, 2019) and through the use of guided inquiry-based student worksheets can also improve science process skills (Saidaturrahmi, et. al.…”
Section: Article Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Penelitian (Handayani dkk., 2014) Efektivitas penggunaan penuntun praktikum IPA berbasis inkuiri terbimbing diketahui melalui aktivitas siswa, motivasi, dan hasil belajar. Riset (Widyaningrum & Wijayanti, 2019) ada peningkatkan kemampuan kerja ilmiah mahasiswa melalui implementasi buku praktikum biokimia berbasis inkuiri terbimbing dengan peningkatan dari siklus 1 ke siklus 2 sebesar 52,62% dan nilai N-gain sebesar 0,84 (kategori tinggi).…”
Section: Hasil Dan Pembahasanunclassified